Analisa Hubungan Antara Disiplin Kerja, Budaya Organisasi Dengan Kinerja Karyawan Dalam Perusahaan - Dedy Syahyuni* (LPPM Universitas BSI, 2020)
In this fast-paced era like today, an organization in this case the company is also required to be able to work quickly in addition to being effective and efficient. Therefore, it cannot be denied, there is a high expectation of the performance of the employees in each company. Employees are asked to be able to provide the achievement of these expectations. Both expectations as individuals and as part of a work team. Because so many things that need to be considered in improving performance, the company must pay attention to some of these things. Two of them are good work discipline and ideal work culture. Both of these are not determinants of performance but these two things are a development of employee performance. The purpose of this paper is to provide an overview of work discipline and organizational culture and their contrubution on the creation of employee performance. In this paper, the results show that work discipline variables and organizational culture are related to 0.636, which means there is a strong relationship and gives an effect of 40 percent on the formation of employee performance. Keywords: Dicipline, organizational culture, work Performance